Long-Term Changes in Weight in Patients With Severe and Complicated Obesity After Completion of a Milk-Based Meal Replacement Programme - Abdalgwad, Razk; Rafey, Mohammed F.; Foy, Siobhan; Newell, Micheál; Davenport, Colin; O'Keeffe, Derek T.; Finucane, Francis M. (Frontiers in Nutrition, 2020)
Introduction: Even with very significant short term weight loss with intensive dietary restriction, subsequent weight regain remains a challenge for most patients. We sought to assess long-term weight change in patients with obesity following completion of a 24-week milk-based meal replacement programme. Methods: We conducted a retrospective cohort study of bariatric patients who completed our milk-based meal replacement programme. This programme started with an 8-week weight loss phase, followed by weight stabilisation (8 weeks) and weight maintenance (8 weeks) phases, after which patients were followed up in the bariatric outpatient clinics. A paired sample t-test was used to compare mean differences in weight at the start and the end of the programme and at follow-up. Linear regression was used to identify predictors of weight regain. Results: In total, 78 patients had long term follow-up data at a mean of 34.4±19.8 months after the start of the milk diet and were included in this analysis. Mean body mass index at baseline was 50.5±7.6 kg m-2, 41 (52.6%) were female and the mean age was 51.6±12.0 (range 18.0-71.5) years. Weight decreased from144±26 kg at the start of the milk diet to 121.2±24 kg at completion (P <0.001), with a non-significant trend upwards in the first and second years of follow-up to 129.0±27.7 (P=0.07 compared to nadir) and 123.4±29.0kg (P=0.17), respectively. Although regains in the third and fourth follow-up years were substantial to 131.0±22.3 (P<0.001), and 139.8±35.4 kg (P<0.001), there was still a moderate net weight loss of 4.7 [9.5, 0.21] and 7.0 [13.9, 0.26] kg (both P=0.04) between the start and the third and fourth follow-up years, respectively. The amount of weight regain was inversely associated with weight loss at completion of the programme, age, and directly associated with the duration of follow up in months (β=1.2 [0.46, 1.9] P=0.002). Conclusion: In Patients with severe obesity who completed a milk-based meal replacement programme and lost a large amount of weight, over four years of follow-up there was very substantial weight regain. Greater initial weight loss and older age were associated with less subsequent weight regain.